ACCOUNTING PRINCIPLES: THEIR GENERAL ACCEPTANCE AND APPLICATION. - Hylton, Delmer P. (The Accounting Review, 1954)
Abstract The purpose of this article is to examine some of the factors involved in the present concept of generally accepted accounting principles as well as their application. Even though no formal, codified set of accounting principles exists, there is general agreement among those who prepare and use financial statements as to the basic principles. The concepts of the going concern, matching of income with related expense, and cost as an original measure of value are probably unchallenged. Conservatism, or the postulate of anticipate no profits and provide for all probable losses is likewise widely accepted. The following criterions are suggested as a means of selecting those who might assume the responsibility for determining standards of application as well as principles: a demonstrated proficiency in accounting and an interest in accounting as a rational subject, per se. In seeking those who satisfy the first requirement, an acceptable though not infallible guide is the C.P.A. certificate. Finding those who also satisfy the second requirement is more difficult. However, practicing certified public accountants and college instructors in accounting should in general satisfy this second requirement.